(untitled) (PERcursos Linguísticos, 2019)
This article presents a narrative and some reflections on critical literacy practices in the English language teaching and learning for 2-5 year old children, demonstrating how these practices can contribute to the rupture with pre-established social standards. In addition, we discussed the education of English teachers, reflecting on the lack of initial and continuing education for graduates who wish to work in early childhood education. Likewise, we consider how existing training can culminate in practices that help children’s English teaching and learning to take place in a critical and questioning way. Moreover, we think about the motivations that encourage English in early childhood education, whether for marketing or for identity, social, cultural issues. Keywords: English teaching. Children. Critical education.